The Controversy of Trade in Tobacco and Protection ofPublic Health, A Study of Tobacco Control Measures andImpacts on Trademark Practice: The Stricter, The Better? - Suwan-in, Nattapong (UI Scholars Hub, 2014)
This paper investigates the anticipated trademark problems may result from tobacco control regulations, particularly the warning label requirements implemented in WTO members and the stricter regulation of plain packaging promulgated in Australia (“tobacco measures”). Following the adoption of the Framework Convention on Tobacco Control (“FCTC”) in May 2003 (enforce by February 2005), member countries tend to seek for possibilities to implement and use stricter approach to achieve their public health policy. As the core concept and main goal of WTO is trade liberalization, regardless of types of goods traded among members, whereas the stricter restriction on trademark use means the prohibition of exploiting intellectual property rights of trademark owners, TRIPS is thus unavoidably related and has been brought by tobacco companies to be against the regulations, claiming that this poses unjustifiable trade barriers to business and denying its legitimacy in corresponding to the WTO obligations. To what extent the FCTC instructs or entitles members to pose barriers on trade in tobacco basing on public health purpose? Is there any correlation between the FCTC, a framework adopted under World Health Organization (“WHO”), and the covered agreements under WTO such as TRIPS?